2006
DOI: 10.1084/jem.20061519
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G/3F mediates intrinsic resistance of monocyte-derived dendritic cells to HIV-1 infection

Abstract: HIV-1 infects immature dendritic cells (iDCs), but infection is inefficient compared with activated CD4+ T cells and only involves a small subset of iDCs. We analyzed whether this could be attributed to specific cellular restrictions during the viral life cycle. To study env-independent restriction to HIV-1 infection, we used a single-round infection assay with HIV-1 pseudotyped with vesicular stomatitis virus G protein (HIV-VSVG). Small interfering RNA–mediated depletion of APOBEC3G/3F (A3G/3F), but not TRIM5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 28 publications
4
86
0
1
Order By: Relevance
“…It could be due to the possible inhibition of APOBEC3G on viral RNA packaging (50). Furthermore, we and others have identified that APOBEC3G in the resting CD4 cells and myeloid dendritic cells can effectively inhibit the incoming HIV-1 viruses (30,51,52). This inhibition is also unlikely contributed by its cytidine deaminase activity.…”
Section: Discussionmentioning
confidence: 98%
“…It could be due to the possible inhibition of APOBEC3G on viral RNA packaging (50). Furthermore, we and others have identified that APOBEC3G in the resting CD4 cells and myeloid dendritic cells can effectively inhibit the incoming HIV-1 viruses (30,51,52). This inhibition is also unlikely contributed by its cytidine deaminase activity.…”
Section: Discussionmentioning
confidence: 98%
“…This prevents detection of reverse‐transcribed viral DNA and activation of interferon responses (Gao et al , 2013; Bridgeman et al , 2015; Gentili et al , 2015). Other factors contributing to HIV‐1 escape in DCs have been described and include TREX1, an exonuclease that degrades reverse‐transcribed HIV DNA in the cytoplasm (Yan et al , 2010), and APOBEC3G/3F (A3G/3F) whose knockdown enhances HIV‐1 infection of DCs associated with G‐to‐A hypermutation of the HIV genome (Pion et al , 2006). These observations explain how HIV‐1 avoids innate sensing during uptake into DCs and in the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased A3G expression and susceptibility to HIV-1 occurs during differentiation of human monocytes to monocyte-derived macrophages (13). Conversely, increased A3G expression with enhanced resistance to HIV-1 occurs during dendritic cell maturation (14). Finally, decreased levels of A3G have been noted in the CD4 ϩ T helper 2 (Th2) subset, compared with T helper 1 (Th1) cells (15).…”
mentioning
confidence: 96%